Power to the people constitutionalism after populism - Tushnet, Mark V. 1945-; Bugarič, Bojan (Oxford University Press, 2021)
What is constitutionalism? The only sensible follow-up is, Why do you want to know? Scores of books have been written offering scores of descriptions of constitutionalism: descriptions of the real world of constitutions and prescriptions for the authors' "best" account of constitutionalism as a system of values. Each author has in mind some purpose for which she is providing the description. As should be clear already, our purpose is to provide some leverage on the analysis of contemporary populism. That purpose sets some important guidelines for our answer to the question posed in the Chapter's title. Because we are interested in contemporary populism, we are interested in contemporary constitutionalism. We aren't going to spend time on describing "Athenian" constitutionalism, or "medieval" constitutionalism, although for other purposes examining those and many other forms of constitutionalism would be quite valuable. More important, we aren't going to discuss constitutionalism as what philosophers call a "regulative ideal" - a reasonably comprehensive set of values that we could use as a benchmark against which we could measure actual constitutional performance. Consider a relatively simple question: Are laws against hate speech consistent with constitutionalism as a regulative ideal? On some accounts, clearly no - such laws violate ideals of freedom of expression. On other accounts, clearly yes - such laws are required to ensure that everyone can participate in civic life on an equal basis. Proponents of each view will of course provide elaborate arguments rooted in stories about individual autonomy, democratic self-governance, and the like to justify their particular view of constitutionalism as a regulative ideal. Precisely because each view is reasonable - as are many others - we think it unhelpful to rely on "regulative ideal" versions of constitutionalism in our inquiry into the relation between contemporary constitutionalism and contemporary populism"--